Method for preparing micro-nano zero-valent iron material with high dehalogenation activity through micro-moisture ball milling

Prepare high -marinated activity through micro -tide grinding method, to solve the problem of low activity of micro -NVI materials in traditional ball milling methods, and realize the rapid degradation of halogen organic matter and stability under high pH conditions. Essence

CN119346878AActive Publication Date: 2025-01-24ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411452736.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The micro-nano ZVI materials prepared by traditional dry ball milling have low dehalogenation activity, and the preparation process involves cold welding of materials, insufficient grinding and unstable quality.

Method used

The micro-tide ball milling method is used to mix iron powder with dodecyldimethyl betaine (BS-12) and a trace amount of water to form a slightly moist material with a moisture content of 1.5% to 6%, and mix it with the ball milling medium. Ball milling to prepare micro-nano zero-valent iron materials with high dehalogenation activity.

Benefits of technology

It has significantly improved the activity of micro-navi materials, has a fast rate of degradation of halogen organic matter, and still maintains good activity under high pH conditions, and the degradation efficiency is increased by 24-80 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346878A_ABST
    Figure CN119346878A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a micro-nano zero-valent iron material with high dehalogenation activity by micro-moisture ball milling. The micro-nano zero-valent iron material is prepared by mixing and ball-milling a trace amount of water, iron powder and a modified substance as raw materials according to a certain proportion. The material can be used for in-situ remediation treatment of underground water containing chlorine organic pollutants, has higher activity compared with a dry ball-milled zero-valent iron material, can completely remove a target pollutant trichloroethylene within 1 hour at the soonest, has better pH adaptability, and still has higher degradation efficiency under an alkaline condition. The micro-nano ZVI prepared by the micro-moisture ball milling method and the modified material of the micro-nano ZVI are environment restoration materials which are low in cost, high in restoration efficiency, green and low in carbon, are easy to popularize and have better environmental and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental materials, and specifically relates to a method for preparing micro-nano zero-valent iron material by a micro-tidal ball milling method and application thereof. Background Art

[0002] Zero-valent iron (ZVI) is an active metal with a low standard redox potential (E0 = -0.44V). It is non-toxic, abundant in resources, cheap and easy to produce. It is widely used to reduce inorganic or organic pollutants in the degradation environment. Ball milling is a common method for preparing micro-nano ZVI. High-energy ball mills use high-speed rotating grinding media (usually steel balls, zirconium balls, etc.) to strongly impact, shear, rub and collide iron powder, thereby refining the particles to form micro-nano ZVI. Traditional ball milling micro-nano ZVI preparation methods can be divided into dry (anhydrous) ball milling and wet (aqueous solution or organic solvent) ball milling. Dry ball milling is prone to cold welding of materials, insufficient grinding, and uneven mixing of materials. Wet ball milling requires a large amount of aqueous solution as a ball milling medium, which has problems such as short material life and unstable quality. Factors such as ball mill type, rotation speed, material and specifications of ball mill jars and grinding balls will affect the physicochemical properties and activity of the material. In order to further improve the activity of ball-milled micro-nano ZVI, a large number of scholars have studied the element doping method such as C / N / S / P or the surfactant modification method. These methods have certain effects but undoubtedly increase the preparation cost of the materials and may also cause secondary pollution in the actual application of the materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing micro-nano zero-valent iron materials with high dehalogenation activity by a micro-tidal ball milling method, in view of the problem that the micro-nano ZVI materials prepared by the existing traditional dry ball milling method have low dehalogenation activity. The method has abundant raw material sources, simple operation, and is green and low-carbon. Compared with traditional ball milling materials, the activity of the prepared micro-nano ZVI is significantly improved, it has a fast degradation rate for halogenated organic matter, and still has good activity under high pH conditions.

[0004] The technical solutions specifically adopted in the present invention are as follows:

[0005] In the first aspect, the present invention provides a method for preparing a micro-nano zero-valent iron material with high dehalogenation activity by a micro-tidal ball milling method, wherein iron powder and dodecyl dimethyl betaine (BS-12) are used as solid phase materials, the solid phase materials are mixed with a trace amount of water to form a slightly moist state material with a moisture content of 1.5% to 6%, and then the slightly moist state material is mixed with a ball milling medium for ball milling to obtain a micro-nano zero-valent iron material.

[0006] Preferably, the iron powder is scrap iron and / or zero-valent iron powder.

[0007] Preferably, the water is deionized water.

[0008] Preferably, the solid phase material further contains a modifying substance, and the modifying substance is at least one of sulfur powder and nickel powder.

[0009] Preferably, the solid phase material is mixed with dodecyl dimethyl betaine (BS-12), sulfur powder and iron powder in a mass ratio of (2-10):(10-20):100.

[0010] Preferably, the solid phase material is mixed with dodecyl dimethyl betaine (BS-12), nickel powder and iron powder in a mass ratio of (2-10):(15-25):100.

[0011] Preferably, the ball mill is a planetary ball mill with a rotation speed of 300 to 800 rpm and a time of 6 to 24 hours.

[0012] Preferably, the ball milling medium is a stainless steel ball, a cemented carbide ball, a zirconia ball, an alumina ball, a ceramic ball, or an agate ball. The diameter of the ball milling medium is 1 mm to 10 mm, and the filling mass of the ball milling medium is 8 to 30 times the mass of the material in the slightly moist state.

[0013] Preferably, the mixing mass ratio of water to solid phase material is (2-4):100, and more preferably 3:100.

[0014] In a second aspect, the present invention provides a micro-nano zero-valent iron material with high dehalogenation activity prepared by the method described in any one of the schemes of the first aspect above.

[0015] In a third aspect, the present invention provides an application of the micro-nano zero-valent iron material with high dehalogenation activity as described in the second aspect in wastewater treatment or environmental remediation.

[0016] Preferably, in the above application, the micro-nano ZVI material can be used for in-situ remediation of groundwater containing chlorine-containing organic pollutants. The chlorine-containing organic pollutants can be vinyl chloride, dichloroethylene, trichloroethylene, tetrachloroethylene and other vinyl chlorides, trichloroethane, tetrachloroethane and other chloroethanes, and carbon tetrachloride, etc.

[0017] Compared with the existing micro-nano ZVI material ball milling technology, the present invention has the following beneficial effects:

[0018] (1) The micro-nano ZVI material prepared by the method of the present invention significantly improves the degradation efficiency of organic chlorinated pollutants in groundwater. When the same pollutant removal effect is achieved, the required repair time is shorter. The degradation rate of trichloroethylene can be increased by 24-80 times.

[0019] (2) The micro-nano ZVI material prepared by the method of the present invention has high stability and durability when used for removing organic chlorinated pollutants in groundwater, and has excellent degradation efficiency under weak acid, neutral, weak base and strong base conditions of pH = 6 to 13. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope (SEM) images of the micro-nano S-ZVI materials prepared in Example 1 and Comparative Example 1;

[0021] Figure 2 The graph is a particle size measurement result of the micro-nano S-ZVI material prepared in Example 1 and Comparative Example 1;

[0022] Figure 3 This is a trichloroethylene degradation diagram of the modified micro-nano S-ZVI material prepared in Example 1;

[0023] Figure 4 The trichloroethylene degradation diagram of the micro-nano S-ZVI material prepared in Example 1 and Comparative Examples 1 and 2 is shown in FIG.

[0024] Figure 5 It is the trichloroethylene degradation diagram of the modified micro-nano S-ZVI material prepared in Example 1 (corresponding to the 3:100 group) and Example 2 (corresponding to the 1.5:100, 4.5:100, and 6:100 groups);

[0025] Figure 6 It is the trichloroethylene degradation diagram of the micro-nano Ni-ZVI material prepared in Example 3 and Comparative Example 3;

[0026] Figure 7 This is a diagram of trichloroethylene degradation of the micro-nano ZVI materials prepared in Example 4 and Comparative Example 4. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The present invention proposes a green preparation method for high-activity micro-nano ZVI - micro-tidal ball milling. The method for preparing micro-nano zero-valent iron materials with high dehalogenation activity based on micro-tidal ball milling is: using iron powder and dodecyl dimethyl betaine (BS-12) as solid phase materials, mixing the solid phase materials with trace water to form a slightly moist state material with a moisture content of 1.5% to 6%, and then mixing the slightly moist state material with a ball milling medium for ball milling to obtain micro-nano zero-valent iron (ZVI) material.

[0029] The iron powder used in the present invention can be at least one of scrap iron or zero-valent iron powder. The water used is preferably deionized water. In addition, in addition to the iron powder and BS-12, the solid phase material can further contain a modified substance, which is at least one of sulfur powder and nickel powder, and the modified micro-nano ZVI material prepared in this way is obtained.

[0030] Unlike traditional methods, this method only requires the addition of trace amounts of water to ball-mill zero-valent iron and its modified materials in a micro-humid environment to obtain highly active micro-nanoscale ZVI materials. The innovation of this micro-humidity ball milling method is that during the high-energy ball milling process, after the introduction of trace amounts of water, the collision between the raw material particles and the grinding balls generates instantaneous high temperatures at the interface, and the water will vaporize into water vapor. The fresh surface formed by the fracture and crushing of the material particles during the ball milling process will interact with the water vapor: first, the water vapor reacts with the iron surface to generate gas, gradually exposing the microcrystalline surface to form new pores. These pores are further expanded or merged in the subsequent ball milling process to generate larger pore structures; second, during the collision and grinding process between particles, the water vapor acts as a material dispersant to avoid material agglomeration, which can promote further refinement of the iron powder and improve the uniformity and activity of the material; third, under high-temperature ball milling conditions, the water vapor may undergo a pyrolysis reaction to form hydrogen and oxygen. The reaction usually occurs between 700 and 1,000 degrees Celsius, but with the continuous input of mechanical energy, it may decompose at a lower temperature, and the generated hydrogen further improves the reduction performance of the material during the reaction. The good activity of the micro-nano ZVI material obtained under this condition has been fully confirmed by multiple groups of experiments.

[0031] In short, the addition of trace amounts of water during the high-energy ball milling process can introduce fresh surfaces and a large number of defects into the micro-nano ZVI, thereby accelerating diffusion, phase change, and mechanochemical reactions, thereby significantly enhancing the performance of the micro-nano ZVI in terms of microstructure and activity.

[0032] The technical effect of preparing micro-nano zero-valent iron materials with high dehalogenation activity based on the micro-tidal ball milling method is demonstrated below through multiple embodiments and comparative examples.

[0033] Example 1 (Micro-nano S-ZVI micro-tidal ball milling method)

[0034] In this embodiment, a modified sulfurized micro-nano ZVI material (micro-nano S-ZVI) is prepared by a planetary ball mill micro-tidal ball milling method, and the steps are as follows: 90g of stainless steel balls (particle size 6mm×50 and 10mm×10) are loaded into a ball mill; 0.1g BS-12, 0.322g sulfur powder, 2.8g iron powder and 0.1g deionized water (sulfur iron mass ratio is 11.5:100; water mass percentage in the total material is 3%) are weighed and placed in a ball mill, the ball mill is sealed and placed in a ball mill; the ball mill is turned on, the ball mill speed is adjusted to 400 rpm, and the ball mill is performed for 17 hours; after the ball milling is completed, the ball milling medium and the ball milling product are separated under a nitrogen atmosphere to obtain a modified micro-nano S-ZVI material.

[0035] The scanning electron microscope morphology (SEM) and particle size measurement results of the two modified micro-nano S-ZVI prepared by the micro-tidal ball milling method in Example 1 and the conventional dry milling method in the subsequent comparative example 1 are shown in FIG. Figure 1 , Figure 2 As shown, the data indicate that the material prepared by micro-tidal ball milling has a rougher surface morphology than that prepared by dry grinding, and contains a large number of tiny flakes <3 μm, and the specific surface area of ​​the particles is increased by 1 times.

[0036] The degradation efficiency of the above materials was tested with trichloroethylene as the target pollutant. 0.2g of modified sulfide zero-valent iron material was added to a 40mL vial, and 20mL of deoxygenated ultrapure water or deoxygenated HEPES buffer solution of pH 7, 11, and 13 was added. The bottle mouth was plugged with a butyl rubber stopper and sealed with an aluminum cap. Then, the trichloroethylene stock solution was injected into the bottle to make the initial concentration of trichloroethylene in the bottle 10ppm, and then placed on a rotary mixer to react at 30 rpm and 25°C. The trichloroethylene concentration was measured at certain time intervals.

[0037] The degradation effects of the modified micro-nano S-ZVI material in different solution systems are shown in Tables 1 and Figure 3 As shown, the degradation of trichloroethylene in pure water by the material prepared by the micro-tidal ball milling method, the material prepared by the dry ball milling method in Comparative Example 1, and the material prepared by the wet ball milling method in Comparative Example 2 is shown in FIG. Figure 4 shown.

[0038] Table 1

[0039]

[0040] It can be seen from Table 1 that in pH 7 buffer and ultrapure water, the modified sulfide zero-valent iron material can remove more than 99% of trichloroethylene within half an hour; as the pH increases, the degradation rate decreases, but trichloroethylene can be basically removed within 2 hours.

[0041] Example 2 (Micro-nano S-ZVI micro-tidal ball milling method: different water-solid ratios)

[0042] In this embodiment, a modified sulfurized micro-nano ZVI material (micro-nano S-ZVI) was prepared by a planetary ball mill micro-tidal ball milling method, and the steps were as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) were loaded into a ball mill; 0.1 g of BS-12, 0.322 g of sulfur powder, 2.8 g of iron powder and different masses of trace deionized water (sulfur-iron mass ratio of 11.5:100) were weighed and placed in a ball mill, and the ball mill was sealed and placed in a ball mill; the ball mill was turned on, the ball mill speed was adjusted to 400 rpm, and the ball milling was performed for 17 hours; after the ball milling, the ball milling medium and the ball milling product were separated under a nitrogen atmosphere to obtain a modified micro-nano S-ZVI material.

[0043] Using the same conditions as in Example 1, the degradation effects of S-ZVI materials obtained by micro-tidal ball milling with deionized water of different masses and the materials obtained by micro-tidal ball milling in Example 1 on trichloroethylene in pure water were measured in deoxygenated ultrapure water as shown in Tables 2 and Figure 5 shown.

[0044] Table 2

[0045]

[0046] Example 3 (Micro-Nano Ni-ZVI Micro-Tidal Ball Milling Method)

[0047] In this embodiment, a modified micro-nano nickel-doped zero-valent iron material (Ni-ZVI) is prepared by a micro-tidal ball milling method using a planetary ball mill, and the steps are as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) are loaded into a ball mill; 0.1 g of BS-12, 0.588 g of nickel powder, 2.8 g of iron powder and 0.1 g of deionized water (the mass ratio of nickel to iron is 21:100; the mass percentage of water in the total material is 2.8%) are weighed and placed in a ball mill, and ball milling is started. The ball milling conditions are the same as in Example 1 to obtain a modified micro-nano Ni-ZVI material.

[0048] The degradation activity of the material on trichloroethylene was measured in deoxygenated ultrapure water under the same conditions as in Example 1. The results showed that after 30 minutes of reaction, the concentration of trichloroethylene was 0.2 ppm, the degradation efficiency was 98%, and the pseudo-first-order reaction rate constant was 7.74 h -1 The degradation of trichloroethylene in pure water by the modified nickel-doped zero-valent iron material prepared by micro-tidal ball milling and the material prepared by dry ball milling in the subsequent comparative example 3 is shown in the figure Figure 6 As shown, it is shown that the modified nickel-doped zero-valent iron material prepared by the micro-tidal ball milling method of the present invention has obviously better activity.

[0049] Example 4 (Micro-nano ZVI micro-tidal ball milling method)

[0050] In this embodiment, a planetary ball mill is used to prepare a micro-nano ZVI material by a micro-tidal ball milling method, and the steps are as follows: 90g of stainless steel balls (particle size 6mm×50 and 10mm×10) are placed in a ball mill; 0.1g BS-12, 3.1g iron powder and 0.1g deionized water (the mass percentage of water in the total material is about 3%) are weighed and placed in the ball mill, and ball milling is started. The ball milling conditions are the same as in Example 1 to obtain a micro-nano ZVI material.

[0051] The degradation activity of the material on trichloroethylene was measured in deoxygenated ultrapure water under the same conditions as in Example 1. The results showed that after 12 hours of reaction, the concentration of trichloroethylene was 0.6 ppm, the degradation efficiency was 94%, and the pseudo-first-order reaction rate constant was 0.23 h -1 The degradation of trichloroethylene in pure water by the micro-nano ZVI material prepared by micro-tidal ball milling and the material prepared by dry ball milling in the subsequent comparative example 4 is shown in the figure Figure 7 As shown, it is shown that the micro-nano ZVI material prepared by micro-tidal ball milling of the present invention has significantly better activity.

[0052] Comparative Example 1 (Micro-nano S-ZVI dry grinding method)

[0053] In this comparative example, a planetary ball mill was used to prepare a micro-nano S-ZVI material by dry ball milling. The steps were as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) were placed in a ball mill; 0.322 g of sulfur powder and 2.8 g of iron powder (mass ratio of sulfur to iron was 11.5:100) were weighed and placed in the ball mill, and ball milling was started. The ball milling conditions were the same as in Example 1 to obtain a micro-nano S-ZVI material.

[0054] The degradation activity of the material on trichloroethylene was measured in deoxygenated ultrapure water under the same conditions as in Example 1. The results showed that after 12 hours of reaction, the concentration of trichloroethylene was 2.3 ppm, the degradation efficiency was 77%, and the pseudo-first-order reaction rate constant was 0.11 h -1 .

[0055] Comparative Example 2 (Micro-nano S-ZVI wet grinding method)

[0056] In this comparative example, a planetary ball mill was used to prepare a sulfide zero-valent iron material by wet ball milling. The steps were as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) were placed in a ball mill; 0.1 g of BS-12, 0.322 g of sulfur powder, 2.8 g of iron powder (the mass ratio of sulfur to iron was about 11:100) and different masses of deionized water were weighed and placed in a ball mill, and ball milling was started. The ball milling conditions were the same as those in Example 1 to obtain a wet-milled micro-nano S-ZVI material.

[0057] Using the same conditions as in Example 1, the degradation effects of S-ZVI materials obtained by wet grinding with different masses of deionized water on trichloroethylene were measured in deoxygenated ultrapure water as shown in Table 3.

[0058] Table 3

[0059]

[0060] Comparative Example 3 (Micro-Nano Ni-ZVI Dry Grinding Method)

[0061] In this comparative example, a planetary ball mill was used to prepare micro-nano Ni-ZVI material by dry ball milling. The steps were as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) were loaded into a ball mill; 0.588 g of nickel powder and 2.8 g of iron powder (nickel-iron mass ratio of about 21:100) were weighed and placed in the ball mill, and ball milling was started. The ball milling conditions were the same as in Example 1 to obtain dry-milled micro-nano Ni-ZVI material.

[0062] The degradation activity of the material on trichloroethylene was determined under the same conditions as in Example 1. The results showed that after 9 hours of reaction, the concentration of trichloroethylene was 0.6 ppm, the degradation efficiency was 94%, and the pseudo-first-order reaction rate constant was 0.32 h -1 .

[0063] Comparative Example 4 (Micro-nano ZVI dry grinding method)

[0064] In this comparative example, a planetary ball mill was used to prepare micro-nano ZVI material by dry ball milling. The steps were as follows: 90 g of stainless steel balls (particle size 6 mm×50 and 10 mm×10) were loaded into a ball mill; 3.1 g of iron powder was weighed and placed in the ball mill, and ball milling was started. The ball milling conditions were the same as in Example 1 to obtain micro-nano ZVI material.

[0065] The degradation activity of the material on trichloroethylene was determined under the same conditions as in Example 1. The results showed that after 9 hours of reaction, the concentration of trichloroethylene was 7.9 ppm, the degradation efficiency was 21%, and the pseudo-first-order reaction rate constant was 0.004 h -1 .

[0066] The above-described embodiments are only some preferred implementations of the present invention, but are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing micro-nano zero-valent iron materials with high dehalogenation activity by micro-tidal ball milling, characterized in that: Iron powder and dodecyl dimethyl betaine (BS-12) are used as solid materials, the solid materials are mixed with a trace amount of water to form a slightly moist material with a moisture content of 1.5% to 6%, and then the slightly moist material is mixed with a ball milling medium for ball milling to obtain a micro-nano zero-valent iron material.

2. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 1, characterized in that: The iron powder is scrap iron and / or zero-valent iron powder.

3. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 1, characterized in that: The water is deionized water.

4. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 1, characterized in that: The solid phase material also contains a modified substance, and the modified substance is at least one of sulfur powder and nickel powder.

5. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 4, characterized in that: The solid phase material is formed by mixing dodecyl dimethyl betaine (BS-12), sulfur powder and iron powder in a mass ratio of (2-10):(10-20):100; or, the solid phase material is formed by mixing dodecyl dimethyl betaine (BS-12), nickel powder and iron powder in a mass ratio of (2-10):(15-25):

100.

6. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 1, characterized in that: The ball mill adopts a planetary ball mill with a rotation speed of 300 to 800 revolutions per minute and a time of 6 to 24 hours.

7. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in claim 1, characterized in that: The ball milling medium is a stainless steel ball, a hard alloy ball, a zirconium oxide ball, an aluminum oxide ball, a ceramic ball, or an agate ball. The diameter of the ball milling medium is 1 mm to 10 mm, and the filling mass of the ball milling medium is 8 to 30 times the mass of the material in a slightly moist state.

8. The method for preparing micro-nano zero-valent iron material with high dehalogenation activity by micro-tidal ball milling as claimed in any one of claims 1 to 7, characterized in that: The mixing mass ratio of the water to the solid phase material is preferably (2-4):100, and more preferably 3:

100.

9. A micro-nano zero-valent iron material with high dehalogenation activity obtained by the method according to any one of claims 1 to 8.

10. Use of the micro-nano zero-valent iron material with high dehalogenation activity as claimed in claim 9 in wastewater treatment or environmental remediation.

Citation Information

Patent Citations

  • Amphoteric surface micron zero-valent iron and preparation method and application thereof

    CN112139508A

  • Micron zero-valent iron-loaded biochar for removing hexavalent chromium, and preparation method and application thereof

    CN113173608A

  • Nickel and sulfur co-doped nano zero-valent iron as well as preparation method and application thereof

    CN114682260A

  • Method of preparing nano-scale zero-valent iron and application thereof

    WO2017008204A1

  • Method for preparing iron-ferrous sulfide composite

    WO2017075950A1